2012
DOI: 10.1590/s0100-29452012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevivência de Xanthomonas campestris pv. viticola em tecido infectado de videira

Abstract: RESUMO -Tecidos de plantas infectados constituem uma importante fonte de inóculo primário para fitobacterioses. O objetivo deste trabalho foi investigar a sobrevivência de Xanthomonas campestris pv. viticola (Xcv), agente do cancro bacteriano da videira, em tecidos infectados na superfície do solo e durante a compostagem de restos de poda. Mudas de videira 'Festival' foram inoculadas com mutante resistente à rifampicina Xcv2Rif e mantidas em casa de vegetação até apresentarem alta severidade da doença. No prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…Considering standards in banana crops, our results were comparable for N, Mn and Fe, above optimum for P and K, and deficient for Ca, Mg and micronutrients such as Cu and Zn. Our results suggest a potential additional drawback of over-fertilization, as low Ca and Mg could be linked to a reduced absorption caused by high K levels (Baker and Pilbeam, 2007;Hiltunen and White, 2002;Lahav and Turner, 1989), and deficiency in micronutrients may be induced by excessive rates of P (Huang et al, 2000;Singh et al, 1988;Soltangheisi et al, 2013). A comparison to reported enset leaf nutrients in the literature confirms the high K and low Ca levels in our study area (Table 7).…”
Section: Soil Fertility In Relation To Agro-ecological Zones and Manasupporting
confidence: 74%
See 1 more Smart Citation
“…Considering standards in banana crops, our results were comparable for N, Mn and Fe, above optimum for P and K, and deficient for Ca, Mg and micronutrients such as Cu and Zn. Our results suggest a potential additional drawback of over-fertilization, as low Ca and Mg could be linked to a reduced absorption caused by high K levels (Baker and Pilbeam, 2007;Hiltunen and White, 2002;Lahav and Turner, 1989), and deficiency in micronutrients may be induced by excessive rates of P (Huang et al, 2000;Singh et al, 1988;Soltangheisi et al, 2013). A comparison to reported enset leaf nutrients in the literature confirms the high K and low Ca levels in our study area (Table 7).…”
Section: Soil Fertility In Relation To Agro-ecological Zones and Manasupporting
confidence: 74%
“…From our observations, two potential mechanisms on how nutrient levels may influence Xanthomonas susceptibility are in line with the data. First, excessive rates of P may interfere with micronutrient uptake (Huang et al, 2000;Singh et al, 1988;Soltangheisi et al, 2013), and micronutrient deficiencies have been shown to increase susceptibility to Fusarium wilt in banana crops (Hecht-Buchholz et al, 1998). In our study area, a significantly higher P av was observed in the soils of symptomatic farms, while an imbalance in micronutrients is likely based on the leaf analysis reported (Tables 3 and 7; Fig.…”
Section: Effects Of Altitude and Nutrients On Xanthomonas Wilt Diseasmentioning
confidence: 71%
“…Disease progression can be slowed down to some extent by implementing strong sanitation pruning, thereby reducing yields but avoiding the death of plants. Nonetheless, the pathogen was reported to survive for at least 80 days in grapevine‐infected tissues on the soil surface (Silva et al., 2012 ).…”
Section: Entrymentioning
confidence: 99%
“…O patógeno sobrevive em videira e outras hospedeiras infectadas, com ou sem sintomas (NASCIMENTO; MARIANO, 2004;PEIXOTO et al, 2007) e em restos culturais (SILVA et al, 2012). Destas fontes de inóculo, Xcv é disseminada durante os tratos culturais por respingos de água de chuva e irrigação, pulverizações, ferramentas de cultivo não desinfestadas, roupas e veículos (NASCIMENTO; MARIANO, 2004).…”
Section: Introductionunclassified